Market Orientation of Multinational Corporations Operating in Turkey and Its Impact on Firms Operations - Cagatay, Zeynep (2008)
This research intends to deeply analyze the implementation of market orientation concept by multinational corporations operating in Turkish business context. Until this time, the research has focused on developed countries, especially the USA and European countries and almost ignored the developments in developing countries. For that reason, this research is worth doing due to its intention to fill the gap in the marketing literature by focusing on market orientation in a developing country, namely, Turkey, as well by analysing the operations of MNCs rather than examining national firms in Turkey.